Days you were mine : [large type] a novel - Hall, Clare Leslie (Thorndike Press large print dynamic drama., 2025)
"Luke and Hannah live a happy and stable life in London, working in jobs they love as they prepare for the arrival of their first child, Samuel. All his life, Luke has known he was adopted, but he's never felt the need to seek out his birth mother--until he becomes a father himself. Spurred by the connection he feels to his son, Luke's search leads him to his birth mother Alice. Their first encounter is surreal, a sharp prick that barely scratches the surface of a painful past that neither of them has fully confronted. Alice sinks into memories of her life as a young artist in 1970s London, and of her tragic whirlwind romance with an enigmatic musician who would become Luke's father. Meanwhile, Luke spirals as he comes face to face with his feelings of abandonment that he worked so hard to bury. But at least Alice seems keen to make up for lost time by looking after Samuel--until her doting grandmother act takes a sinister turn for the worse. As the truth of who Alice is and the story behind her heartbreaking decision to give up her baby come to light, she and Luke must reckon with the sacrifices they've made in the pursuit of love and belonging"--